Pengembangan Media Pembelajaran Alternatif Phantom Injeksi Modifikasi Pada Kegiatan Praktikum di Laboratorium Keperawatan - Aminatul Fitri; Putra Mulia; Eka Febriyanti (HEALTH CARE : JURNAL KESEHATAN, 2021)
Activities in the laboratory are directly related to learning media, one of which is injection props. The high need for borrowing and using teaching aids and the existence of nursing laboratory standards make PLP have to innovate related to finding new alternatives to complement the shortage of teaching aids. This study aims to determine the reliability of modified injection phantom in improving the cognitive, affective, and psychomotor aspects of students in practical activities in the nursing laboratory. This research was conducted at the Laboratory of the Faculty of Nursing, University of Riau, in March – November 2020. The samples in this study were 20 students and 5 lecturers. The research method used is Research and Development (R&D), the steps that researchers use in research and development of learning media refer to the design developed by Borg and Gall. The results of this study indicate that the modified injection phantom developed is considered to be able to be used as a phantom or alternative injection props based on existing needs and the media that has been developed can be used for practicum because it has a good general and special appearance. Suggestions for further researchers are expected to be able to develop modified injection phantom learning media in order to improve existing prototypes